A Report on 15 Years of Clinical Negligence Claims in Rhinology. Issue 6 (November 2014) - Geyton, Thomas; Odutoye, Tunde; Mathew, Rajeev
Background: This study was designed to determine the characteristics of medical negligence claims in rhinology. In 2010–2011 the National Health Service (NHS) litigation bill surpassed 1 billion Great British Pounds (GBP; 1.52 billion U.S. dollars [US]). Systematic analysis of malpractice complaints allows for the identification of errors and can thereby improve patient safety and reduce the burden of litigation claims on health services. Methods: Claims relating to ear, nose, and throat between 1995 and 2010 were obtained from the NHS Litigation Authority and were analyzed. Results: The series contains 65 closed claims that resulted in payment totaling 3.1 million GBP (US4.7 million). Fifty claims were related to surgical complications. Functional endoscopic sinus surgery and septoplasty were the procedures most commonly associated with successful claims. There were 11 cases of orbital injury including 6 cases of visual loss and 5 cases of diplopia. The most common cause of a claim was failure to recognize the complication or manage it appropriately. Lack of informed consent was claimed in eight cases. Other claims arose because of errors in outpatient procedures (two), diagnosis (six), delayed surgery (one), and errors in medical management (three). Conclusion: This is the first study to report the outcomes of negligence claims in rhinology in the United Kingdom. Claims in rhinology are associated with a high success rate. Steps that can be taken to reduce litigation include careful patient workup and ensuring adequate informed consent. Where there is a suspicion of orbital damage early recognition and intervention is needed to reduce long-term injury to the patient.